Immune phenotyping of diverse syngeneic murine brain tumors identifies immunologically distinct types - Jasneet Kaur Khalsa (Nature Portfolio, 2020)
Syngeneic mouse models for glioblastoma (GBM) cannot fully recapitulate clinical findings and response to therapy in patients. Here the authors perform a comprehensive immune profiling of different syngeneic GBM tumour models and compare it with the immune landscape of GBM patients to identify similarities and potential confounding differences.